Kerja berpasukan berdasarkan team player survey (PTPS): satu kajian di dua buah organisasi pengeluaran elektronik di Sarawak - Fauziah, Ariyon (Universiti Malaysia Sarawak (UNIMAS), 2004)
The purpose of this study is to look at the differences of teamwork style in TOKO Sdn Bhd and Komag USA (Malaysian). This study is also to identify the relationship between selected demographical factors (post, sex, marital status, length of service) and the four teamwork styles (communicator, collaborator, contributor, challenger) based on Parker Team Player Survey (PTPS). In addition, this study is to identify the most dominant teamwork style in both studied organizations. 78 respondents (50 from Komag and 28 from Tako) are chosen randomly. 3 respondents from the managerial department of each organization are chosen to be interviewed. The result reveals that different organization does not has any influence on employee's teamwork style. Meanwhile, from the demographical aspects of sex, post and marital status, it is found that there is no difference between the factors and the teamwork style. However, there is a relationship between age and the communicator style, r = -.305, p <0.01. There is also a relationship between the length of service with the communicator style, r = -.367, p<0.01. Overall, this research shows no differences between both organization and the four teamwork styles. In other words, both Japanese and American organizations have a similar teamwork style. The researcher suggests that future studies of teamwork style take into account to add races as a factor, to test the strength of this research. It is hoped that this study is able to help organization to plan an excellent teamwork strategy.